Therapeutic Drug Monitoring of Levetiracetam and Lamotrigine. Issue 4 (August 2015) - Naik, Girish S.; Kodagali, Rohit; Mathew, Binu S.; Thomas, Maya; Prabha, Ratna; Mathew, Vivek; Fleming, Denise H.
<x xml:space="preserve">Abstract</x> Background: This study was a retrospective assessment of the therapeutic drug monitoring data collected for levetiracetam and lamotrigine from a clinical setting. The proportion of patients in relation to the therapeutic ranges for serum concentrations of lamotrigine and levetiracetam was estimated, and the influence of age and anticonvulsant comedications on their clearances were studied. Methods: Information on levetiracetam (2011–2013) and lamotrigine (2008–2013) dose, trough concentration, age, sex, body weight, and anticonvulsant comedications prescribed was obtained from the therapeutic drug monitoring register and archived medical records. Patients were categorized into 4 groups based on anticonvulsant comedications and further divided into 3 subgroups based on age (a: <9 years; b: 9–17 years; c: ≥18 years). In each subgroup, the proportion of patients who achieved trough concentrations in the therapeutic range for levetiracetam and lamotrigine was computed. Apparent clearance (CL/F) was compared across subgroups by 1-way analysis of variance, and factors which significantly predicted CL/F were identified by stepwise multiple linear regression. Results: Overall, 348 (330 patients) and 706 (493 patients) samples for levetiracetam and lamotrigine were included in the analysis. Of these, 56.9% and 72.4% were within, 43.1% and 23.9% below, 0% and 3.7% above the therapeutic range for levetiracetam and lamotrigine, respectively. A significant difference in CL/F was noted across subgroups for levetiracetam (P < 0.001) and lamotrigine (P < 0.001). Age <9 years, age ≥18 years, and inducer comedications significantly predicted CL/F for levetiracetam. For lamotrigine, inhibitor comedications, age <9 years, inducer comedications, and age 9–17 years significantly predicted CL/F. Conclusions: These findings emphasize the need to monitor relatively newer anticonvulsants, lamotrigine and levetiracetam, especially among children and when other anticonvulsant comedications are prescribed or discontinued in the treatment regimen.